Failsafe display system - Fullalove, Richard Michael (Department of Electrical Engineering, 2016)
A requirement exists to reduce signalling costs on branch lines throughout the South African rail network, by replacing expensive track side signalling with a Radio Token System. The Radio Token System uses a non-failsafe radio data link and non-failsafe printer in the cab. Spoornet intend to replace the printer with a failsafe display in order to eliminate lengthy verbal message protocols and increase safety. This thesis investigates the various concepts of failsafe display, and the means to achieve them. It also investigates the wide range of display technologies available and their suitability for use in a failsafe display. The LED, together with monitoring circuitry, emerges as the most suitable for the application.